Empirical model for fitting the viscosity of lithium bromide solution with CuO nanoparticles and E414 - Li, Jiheng; Wang, Gang; Li, Jitong; Li, Xiao; Liu, Yuexi; Zhang, Qunli (Frontiers in Energy Research, 2023)
To research viscosity fitting model of stable nano-lithium bromide solution (nano-LiBr), the stability of the nano-LiBr and the dynamic viscosity of LiBr were measued by Ultraviolet-visible spectroscopy (UV-vis) and rotational viscometer respectively. Two LiBr with different additives were measured, i.e., LiBr with dispersant (E414) and LiBr with dispersant + copper oxide nanoparticles (CuO). The ranges of measuring temperature were from 25°C–60°C, the concentrations of LiBr were from 50%–59%, the volume fractions of the dispersants were from 0%–4%, and the fractions of nanoparticle volume were from 0%–0.05%. Results indicated that the nano-LiBr with E414 had good stability. The viscosity of the LiBr decreased when temperature increased, and increased when LiBr concentration and dispersant amount were increased. It is also found that the viscosity was directly proportional to the volume fraction of the nanoparticles. This study also showed that the higher the concentration of the base fluid was, the more significant increase of the viscosity was. An empirical viscosity model of stable nano-LiBr with a maximum error of 13% was developed.